Cover image. (10th May 2020) - Wang, Xiangjian; Yang, Jin; Wei, Changlei; Zhou, Gang; Wu, Lanyan; Gao, Qinghong; He, Xin; Shi, Jiahong; Mei, Yingying; Liu, Ying; Shi, Xueke; Wu, Fanglong; et al.
Abstract : The cover image is based on the Original Article A personalized computational model predicts cancer risk level of oral potentially malignant disorders and its web application for promotion of non‐invasive screening by Xiangjian Wang et al., https://doi.org/10.1111/jop.12983 .